Metabonomic analysis of the anti-hepatic fibrosis effect of Ganlong capsules - Lv, ChangLing; Li, YinRui; Ou, Ling; Zhou, Jie; Peng, Fang; Wu, DingYu (Frontiers in Pharmacology, 2023)
Context Liver fibrosis is a progressive liver damage caused by a variety of factors which can progress to cirrhosis and even liver cancer. Many studies have found that metabolic disorders can promote the development of liver fibrosis. Ganlong capsules derived from the Periplaneta americana have been shown to have a therapeutic effect on liver fibrosis. However, the exact molecular mechanism of this hepatoprotective effect is largely unknown. Objective The aim of this study was to investigate the metabolic modulation of Ganlong capsules in hepatic fibrosis. Methods We constructed rats liver fibrosis model with carbon tetrachloride (CCl4) and subsequently administered Ganlong capsules for treatment. The therapeutic effects of Ganlong capsules on liver fibrosis were observed by detecting liver enzyme levels in serum and pathological changes in the liver. In addition, liver tissue, serum and urine non-targeted metabolomics were used to study the metabolic regulatory mechanism of Ganlong capsules on liver fibrosis. Results Ganlong capsules could reduce the level of liver enzymes in the serum of liver fibrosis mice and improve the pathological changes in liver fibrosis mice. Non-targeted metabolomic analysis showed that Ganlong capsule treatment improved metabolic disorders, including glycerophospholipid metabolism, linoleic acid metabolism, butyric acid metabolism, pyrimidine metabolism, glycine, serine and threonine metabolism, valine, leucine and isoleucine biosynthetic pathways, and arachidonic acid metabolism. The above metabolic pathways are important in the formation of CCl4-induced liver fibrosis. Conclusion our study demonstrated the protective effect of Ganlong capsules against hepatic fibrosis. And Ganlong capsule has a good therapeutic effect on liver fibrosis by regulating lipid metabolism, butyric acid metabolism, amino acid metabolism and arachidonic acid metabolic processes.